Deficient IL‐6/Stat3 Signaling, High TLR7, and Type I Interferons in Early Human Alcoholic Liver Disease: A Triad for Liver Damage and Fibrosis. Issue 7 (10th May 2019) - Stärkel, Peter; Schnabl, Bernd; Leclercq, Sophie; Komuta, Mina; Bataller, Ramon; Argemi, Josepmaria; Palma, Elena; Chokshi, Shilpa; Hellerbrand, Claus; Maccioni, Luca; Lanthier, Nicolas; Leclercq, Isabelle
Abstract : Mechanisms underlying alcohol‐induced liver injury and its progression still remain incompletely understood. Animal models can only address some aspects of the pathophysiology that requires studies directly in humans, which are scarce. We assessed liver inflammatory and immune responses at early stages of alcoholic liver disease in a unique cohort of alcohol‐dependent patients undergoing a highly standardized alcohol withdrawal program. In active drinkers, quantitative real‐time polymerase chain reaction revealed alcohol‐induced activation of tumor necrosis factor alpha, interleukin (IL)‐1β, and nuclear factor kappa B in liver tissue already at early disease stages. Double immunofluorescence staining indicated that this proinflammatory response was restricted to activated, CD68‐positive macrophages. In parallel, down‐regulation of IL‐6, inhibition of the signal transducer and activator of transcription 3 (Stat3) pathway, as well as blunted cyclin D expression in hepatocytes, reduced proliferation and favored hepatocyte apoptosis. In addition, immunofluorescence and quantitative real‐time polymerase chain reaction of liver tissue showed that alcohol also activated the toll‐like receptor (TLR) 7–interferon (IFN) axis in hepatocytes, which was confirmed in alcohol‐stimulated primary human hepatocytes and precision‐cut liver slices in vitro . Activation of the TLR7–IFN axis strongly correlated with liver fibrosis markers and disease progression. Two weeks of abstinence attenuated the inflammatory response but did not allow recovery of the defective Stat3 pathway or effect on fibrosis‐associated factors. Conclusion : In humans, inflammation, activation of the TLR7–IFN axis, and inhibition of Stat3‐dependent repair mechanisms in early alcoholic liver disease pave the way for fibrosis development and ultimately disease progression. Abstract : Why some patients with alcohol dependence develop progressive liver disease remains largely unknown. Here we describe inflammatory and immune mechanisms that increase liver damage and impair liver regeneration and repair. These changes already operate at early stages of alcoholic liver disease in humans. They likely prepare an environment that favors progression of liver disease if drinking habits persist and could constitute a future target for therapy.